State funds in the light of Polish Financial Law - Juchnevicius, Edvardas (Bulletin of the Karaganda University “Law Series”, 2023)
This paper presents a comparative analysis of state special funds in Poland, focusing on their legal dimensions within the framework of financial law. State special funds play a vital role in the allocation and management of public resources, serving as targeted financial mechanisms to address specific needs and promote socio-economic development. However, there is limited comparative research examining the legal frameworks and operational aspects of these funds in different jurisdictions. This study aims to fill this gap by conducting a comprehensive analysis of state special funds in Poland, providing valuable insights into their legal frameworks, objectives, structures, and operational mechanisms. The research objectives of this study include examining the legal frameworks governing state special funds in both countries, analyzing their objectives and operational mechanisms, identifying similarities and differences, and assessing their effectiveness and challenges. By achieving these objectives, this study aims to contribute to the enhancement of financial law practices in both jurisdictions and provide knowledge for improving the legal frameworks and operational efficiency of state special funds.